2018
DOI: 10.1016/j.scitotenv.2018.02.329
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of rice husk derived activated carbon for removal of nitrate contamination from water

Abstract: Development of porous carbons with high specific surface area (>1200mg) targeted at nitrate removal from aqueous solutions is investigated by chemical activation of carbonized rice husk. Potassium carbonate is used as activating and desilicating agent. The effect of post-synthetic treatment by gas phase ammoxidation with ozone/ammonia or oxidation with concentrated nitric acid followed by nitrification with urea on main physicochemical properties and on the effectiveness of the activated carbons in nitrate rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(33 citation statements)
references
References 54 publications
1
30
0
2
Order By: Relevance
“…Chlorine, the zinc and potassium elements originated from the activation agents (ZnCl 2 and KOH). However, the other elements (Si, S, Ca Cu, Al, Br) are naturally present on the rice straw, and are probably present in residual ashes, similar to the previously published results [31,47,48]. Since their preponderance is lower, we will consider that all ACs are structurally formed by only carbon and oxygen elements.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Chlorine, the zinc and potassium elements originated from the activation agents (ZnCl 2 and KOH). However, the other elements (Si, S, Ca Cu, Al, Br) are naturally present on the rice straw, and are probably present in residual ashes, similar to the previously published results [31,47,48]. Since their preponderance is lower, we will consider that all ACs are structurally formed by only carbon and oxygen elements.…”
Section: Resultssupporting
confidence: 83%
“…Note: Numbers in bold print are statistically significant Table 7 summarizes the EDX quantitative elemental analysis. Data show that the obtained products are essentially composed by carbon and oxygen, as is the case with ACs [47]. Other chemical elements with lower contents are also present (less than 1%).…”
Section: Resultsmentioning
confidence: 68%
“…Rice husk (RH) as an abundant biowaste with low combustion value and damage to the environment can bring the issue of its sustainable utilization . However, RH can be converted to biofuels (e.g., syngas) through the pyrolysis at high temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that activated carbon obtained from RH be used in water and air purification. Moreover, it could be used as anode material for lithium‐ion batteries and for supercapacitors . Rice‐husk pyrolysis has also been used to generate syngas, which can be used to produce electricity …”
Section: Direct Utilization Of Agro‐wastesmentioning
confidence: 99%